enow.com Web Search

Search results

  1. Results from the WOW.Com Content Network
  2. Lenstra elliptic-curve factorization - Wikipedia

    en.wikipedia.org/wiki/Lenstra_elliptic-curve...

    If it does not exist, gcd(n,b) is a non-trivial factor of n. First we compute 2P. We have s(P) = s(1,1) = 4, so the coordinates of 2P = (x ′, y ′) are x ′ = s 2 – 2x = 14 and y ′ = s(xx ′) – y = 4(1 – 14) – 1 = –53, all numbers understood (mod n). Just to check that this 2P is indeed on the curve: (–53) 2 = 2809 = 14 ...

  3. Factorization - Wikipedia

    en.wikipedia.org/wiki/Factorization

    For example, 3 × 5 is an integer factorization of 15, and (x2)(x + 2) is a polynomial factorization of x 2 – 4. Factorization is not usually considered meaningful within number systems possessing division , such as the real or complex numbers , since any x {\displaystyle x} can be trivially written as ( x y ) × ( 1 / y ) {\displaystyle ...

  4. Like terms - Wikipedia

    en.wikipedia.org/wiki/Like_terms

    This means that the common factor variable can be factored out, resulting in ( a + b ) x {\displaystyle (a+b)x} If the expression in parentheses may be calculated, that is, if the variables in the expression in the parentheses are known numbers, then it is simpler to write the calculation a + b {\displaystyle a+b} . and juxtapose that new ...

  5. Quadratic formula - Wikipedia

    en.wikipedia.org/wiki/Quadratic_formula

    The roots of the quadratic function y = ⁠ 1 / 2x 2 − 3x + ⁠ 5 / 2 ⁠ are the places where the graph intersects the x-axis, the values x = 1 and x = 5. They can be found via the quadratic formula. In elementary algebra, the quadratic formula is a closed-form expression describing the solutions of a quadratic equation.

  6. Polynomial expansion - Wikipedia

    en.wikipedia.org/wiki/Polynomial_expansion

    In mathematics, an expansion of a product of sums expresses it as a sum of products by using the fact that multiplication distributes over addition. Expansion of a polynomial expression can be obtained by repeatedly replacing subexpressions that multiply two other subexpressions, at least one of which is an addition, by the equivalent sum of products, continuing until the expression becomes a ...

  7. nth root - Wikipedia

    en.wikipedia.org/wiki/Nth_root

    For example, 3 is a square root of 9, since 3 2 = 9, and −3 is also a square root of 9, since (−3) 2 = 9. The n th root of x is written as using the radical symbol. The square root is usually written as ⁠ ⁠, with the degree omitted.

  8. Elementary algebra - Wikipedia

    en.wikipedia.org/wiki/Elementary_algebra

    For example, taking the statement x + 1 = 0, if x is substituted with 1, this implies 1 + 1 = 2 = 0, which is false, which implies that if x + 1 = 0 then x cannot be 1. If x and y are integers, rationals, or real numbers, then xy = 0 implies x = 0 or y = 0. Consider abc = 0. Then, substituting a for x and bc for y, we learn a = 0 or bc = 0.

  9. Binomial coefficient - Wikipedia

    en.wikipedia.org/wiki/Binomial_coefficient

    As there is zero X n+1 or X −1 in (1 + X) n, one might extend the definition beyond the above boundaries to include () = when either k > n or k < 0. This recursive formula then allows the construction of Pascal's triangle , surrounded by white spaces where the zeros, or the trivial coefficients, would be.